Persepsi Kaum Muda Katolik tentang Manfaat Instagram untuk Membangun Persahabatan - Lutfhi Nur Fahri; Meri anjani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Instagram is a social media platform used to preach the faith. Instagram is a social media trend. The various interesting features on Instagram make the younger generation very close to this social media and can interact with each other. The aim of this research is to determine the perceptions of Catholic youth regarding the benefits of Instagram in building relationships in the Santo Fidelis Sigmaringen Sejiram Parish, West Kalimantan. Qualitative research is used in the writing method of this article. Data was collected through observation, interviews and meetings (FGD). The research results show that the younger generation understands the benefits of Instagram for building relationships. The Instagram account “omkinnocentius_canoura_arnau” makes it easy for the younger generation to receive information about parish activities. Socializing on Instagram can help users build many relationships. This can be seen from the participation of the younger generation who are actively involved in congregational activities. Instagram is a suitable tool to invite many young people to participate in church activities. By actively participating in church activities, young people can build bonds and continue to live out their faith.